Hybrid photovoltaic and thermoelectric generator systems with thermal wheel Ventilation: A sustainable approach to residential heating and cooling - Tian Congxiang; Zhu Guoqing; Yang Yong (Engineering Science and Technology, an International Journal)
The growing need for sustainable energy solutions in residential buildings has driven research into renewable energy integration. While photovoltaic (PV) systems are well-explored, the combination of PV with thermal wheel (TW) systems and thermoelectric generator (TEG) units in thermoelectric ventilation (TEV) systems remains less studied. This paper investigates a hybrid system combining a concentrating PV (CPV)-TEG and a TW-TEV system for residential heating and cooling. Using energy and exergy analysis, two performance indicators, the Energy Proficiency Indicator (PIen) and the Exergy Proficiency Indicator (PIex), were introduced and calculated for a building in Jingzhou, Hubei, China. Results revealed peak PIen and PIex values of 2.44 and 33.55 in September and April, respectively. Additionally, increasing the number of thermoelectric coolers from 10 to 50 enhanced average yearly PIen and PIex by 60.45% and 81.32%. This study’s findings are significant for urban planners and engineers aiming to reduce energy consumption and emissions, offering a practical approach to sustainable building technologies.